(untitled) (Research, Society and Development, 2022)
The present research aims to prepare a literature review on the challenges of hypertensive patients in accessing primary care during the COVID-19 pandemic, identifying the main barriers and/or associated problems and the main contributions of the analyzed works on the subject. Based on the theme, a search strategy was developed using four databases: Analysis of Medical Literature - MEDLINE; Latin American and Caribbean Literature in Health Sciences - LILACS; SCOPUS and Web of Science. To search the databases, indexed and registered descriptors were used, in addition to inclusion and exclusion criteria for selecting the analyzed articles. Eleven (11) articles were selected, where several problems and/or barriers were identified to the access of hypertensive patients to primary health care during the pandemic, highlighting: the lack of access to face-to-face consultations, monitoring and monitoring of their blood pressure blood pressure, deregulation of medication use and delivery, as well as subfactors that also influence the health of these patients. Telemedicine was the main method discussed and evaluated in the works, but other tools were also analyzed, such as mobile phone applications, communication and information technologies that can bring the patient and the health system closer together. Thus, it is concluded that the current global crisis is sanitary, political, economic and social, and requires innovation in health operation modes, always developing new forms of sociability and solidarity in caring for human beings, especially in hypertensive patients.